2018
DOI: 10.1021/acs.jmedchem.8b00613
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Isothiazolo[4,3-b]pyridine-Based Inhibitors of Cyclin G Associated Kinase (GAK) with Broad-Spectrum Antiviral Activity

Abstract: There is an urgent need for strategies to combat dengue and other emerging viral infections. We reported that cyclin G-associated kinase (GAK), a cellular regulator of the clathrin-associated host adaptor proteins AP-1 and AP-2, regulates intracellular trafficking of multiple unrelated RNA viruses during early and late stages of the viral lifecycle. We also reported the discovery of potent, selective GAK inhibitors based on an isothiazolo[4,3- b]pyridine scaffold, albeit with moderate antiviral activity. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…Recently, we reported the discovery of potent GAK inhibitors based on an isothiazolo[4,3 ‐b ]pyridine scaffold, of which compounds 1 , 2 , and 3 are the most promising representatives (Figure ). These compounds display potent GAK affinity ( K d values in the range of 8–80 n m ), are selective, and are also endowed with broad‐spectrum in vitro antiviral activity against HCV, DENV, EBOV, and CHIKV …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we reported the discovery of potent GAK inhibitors based on an isothiazolo[4,3 ‐b ]pyridine scaffold, of which compounds 1 , 2 , and 3 are the most promising representatives (Figure ). These compounds display potent GAK affinity ( K d values in the range of 8–80 n m ), are selective, and are also endowed with broad‐spectrum in vitro antiviral activity against HCV, DENV, EBOV, and CHIKV …”
Section: Introductionmentioning
confidence: 99%
“…Previous explorations of the structure–activity relationship (SAR) of isothiazolo[4,3 ‐b ]pyridines as GAK inhibitors focused on modifications of the functional groups at positions 3 and 6 of the scaffold . In this study, an alternative approach based on scaffold hopping was followed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of action studies confirmed that the inhibition of GAK is an important target underlying the broad-spectrum antiviral activity of compound 51. 115,116 The other chemotype of GAK inhibitor is quin(az)oline, 117,118 yet their antiviral activity was not probed.…”
Section: Kinasesmentioning
confidence: 99%